Company Valuation of an Entity Operating in International Accounting Environment - Hamad, Mirjam; Dékán Tamásné Orbán, Ildikó (International Journal of Engineering and Management Sciences, 2018)
Company and asset valuation plays a major role nowadays. Determining the company’s value is a key factor for management in appropriate decision making, and it is a necessary step for individuals who wish to invest and for investors. There are numerous models which utilize different methods for company valuation. In our study we based our valuation on the McKinsey model for a company in an international accounting environment. In the study we present the main attributes of the McKinley model, its structure, which includes the main steps of valuation. We put a special emphasis on the calculation of free cash flow, future balance sheets and profit and loss accounts anticipation as well as future turnover, which highly influences the changes of data in the future reports thus in the company value. The McKinsey model is a discounted cash flow model, in which the company value and the consequent future cash flow can be determined as present value.